2015
DOI: 10.1016/j.pharep.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide in pharmacology and medicine – An update

Abstract: Hydrogen sulfide (H2S) is the endogenously produced gasotransmitter involved in the regulation of nervous system, cardiovascular functions, inflammatory response, gastrointestinal system and renal function. Together with nitric oxide and carbon monoxide, H2S belongs to a family of gasotransmitters. H2S is synthesized from L-cysteine and/or L-homocysteine by cystathionine β-synthase, cystathionine γ-lyase and cysteine aminotransferase together with 3-mercaptopyruvate sulfurtransferase. Significant progress has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
106
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 169 publications
0
106
0
7
Order By: Relevance
“…Gap junctions between histocytes participate jointly in multiple pathological processes, and they are also widely found in renal tissue. 6,7 It has been found that Cx43 is the most common Cx expressed in the kidney, while Cx45 and Cx40 expressions are also detected to some extent. For normal renal tissue cells, gap junction channel structures closely assembled on adjacent cellular membrane are responsible for information exchange, regulation of messangial cell growth and reproduction, renin secretion, renal blood flow and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions between histocytes participate jointly in multiple pathological processes, and they are also widely found in renal tissue. 6,7 It has been found that Cx43 is the most common Cx expressed in the kidney, while Cx45 and Cx40 expressions are also detected to some extent. For normal renal tissue cells, gap junction channel structures closely assembled on adjacent cellular membrane are responsible for information exchange, regulation of messangial cell growth and reproduction, renin secretion, renal blood flow and so on.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 As the third important gaseous signal molecule in the body after NO and CO, H 2 S is involved in regulating renal function, neuron system, cardiovascular system, inflammatory response and gastrointestinal system. 7 By building diabetic rat model, this research was to observe renal fibrosis and change of Cxs expression in diabetic rats, as well as the influences of H 2 S on myocardial fibrosis and Cxs expression.…”
Section: Introductionmentioning
confidence: 99%
“…Продовжити цей ефект могли б, на наш погляд, речо вини, здатні одночасно пригнічувати активність аргінази (що забезпечувало б збереження L-аргініну для синтезу NO) й інгібувати деградацію гуанозинтрифосфату (що забез-печувало б збереження субстрату для синтезу важливого кофактора спряженого стану сNOS тетрагідробіоптерину (ВН 4 )) [24]. Можли ви ми довготривалими «ліквідато-рами» несп ряження сNOS можуть бути інгібітори інду цибельного синтезу H 2 S, на-приклад, про паргілгліцин [25].…”
Section: результати та їх обговоренняunclassified
“…Hydrogen sulfide (H2S) and nitrogen monoxide (NO) play a significant role in these processes [2,4,10]. Together with carbon monoxide (CO), they belong to the family of gasotransmitters which are involved in the regulation of the physiological functions of the cardiovascular, nervous and digestive systems [10].…”
mentioning
confidence: 99%
“…Endothelial cells release H 2 S and NO in response to different stimuli including insulin, estradiol, acetylcholine, bradykinin, endothelium growth factor (EGF) [2][3][4]. In 2008, there was found that that H 2 S is released not only by smooth muscle cells of the vascular wall, but also by the endothelium [10].…”
mentioning
confidence: 99%